Do Atrial Differences in Endothelial Damage, Leukocyte and Platelet Activation, or Tissue Factor Activity Contribute to Chamber‐Specific Thrombogenic Status in Patients with Atrial Fibrillation?. (22nd November 2013) - JESEL, LAURENCE; ARENTZ, THOMAS; HERRERA‐SIKLODY, CLAUDIA; TRENK, DIETMAR; ZOBAIRI, FATIHA; ABBAS, MALAK; WEBER, REINHOLD; MINNERS, JAN; TOTI, FLORENCE; MOREL, OLIVIER
Atrial Differences in Endothelial Damage, Leukocyte and Platelet Activation Background Thrombi form mainly in the left rather than the right atria of patients with atrial fibrillation (AF), the reason of this predilection being unknown. Objective The purpose of this study was to investigate whether atrial‐specific differences in endothelial damage, leukocyte activation, platelet stimulation, and tissue factor activity occur in patients with AF. Methods Twenty‐two patients (16 men, 6 women; age 56 ± 8 years; 16 paroxysmal AF, 6 persistent AF) with AF undergoing pulmonary vein isolation were investigated. Blood samples from the left and the right atrium were obtained at the start of the procedure. Microparticles (MPs) released by apoptotic/stimulated cells were measured by capture assays. Their procoagulant abilities were quantified by functional prothrombinase and tissue factor assays and their cellular origin were determined (endothelium, platelet, leukocyte). Platelet reactivity was evaluated by whole blood flow cytometry for expression of platelet P‐selectin (CD62P), active glycoprotein IIb/IIIa receptor (PAC‐1). Platelet aggregation was evaluated using ADP, TRAP and collagen‐induced whole blood aggregometry. Results There were no atrial‐specific differences in the levels of total procoagulant MPs, leukocyte‐derived‐MPs or platelet‐derived MPs. Conversely, endothelial‐derived MPs and tissue factor activity and collagen‐induced platelet aggregation were slightly elevated in the right atrium (P < 0.05). Conclusions Our data show no evidence for increased thrombogenic status in the left atrium that would account for its greater propensity for thrombus formation in patients with AF.